2021
DOI: 10.1111/twec.13208
|View full text |Cite
|
Sign up to set email alerts
|

Development aid and illicit capital flight: Evidence from Nepal

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 77 publications
2
8
0
Order By: Relevance
“…This is in line with similar findings by Calì and TeVelde (2011) and Helble et al (2012). More important indeed is to remark that there is evidence that development aid in the form of foreign exchange may, as a side effect, drive trade-related IFFs by import overinvoicing in Nepal, a lower-middle-income country according to UN (Steinkamp and Westermann, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is in line with similar findings by Calì and TeVelde (2011) and Helble et al (2012). More important indeed is to remark that there is evidence that development aid in the form of foreign exchange may, as a side effect, drive trade-related IFFs by import overinvoicing in Nepal, a lower-middle-income country according to UN (Steinkamp and Westermann, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, IFFs may be stimulated by the foreign exchange cash component of received international aid, given that this kind of inflow represents, in a great number of cases, a substantial share of the foreign exchange available to central governments in L&MICs (Reuter, 2012). For example, Steinkamp and Westermann (2021) found that development aid in Nepal in the form of foreign exchange may, as a side effect, drive trade-related IFFs by import overinvoicing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Recent research considers the links between remittances and aid flows and illicit capital outflows. While flows such as development aid are found to be positively correlated with illicit outflows in the presence of capital controls, remittances are negatively correlated with illicit outward capital flight (Steinkamp and Westermann, 2021). Aid may be susceptible to being diverted by the recipient governments, but a similar behavior is unlikely to be tolerated by foreign workers supporting their families back home through remittances.…”
Section: Introductionmentioning
confidence: 93%
“…Some researchers find that global risk is also an important factor in explaining hot money dynamics [24,25]. Steinkamp and Westermann (2021) find that capital flight is positively correlated with development aid in Nepal [26]. Fratzscher et al (2018) find that the Federal Reserve's quantitative easing increased the procyclicality of international portfolio flows [27].…”
Section: Introductionmentioning
confidence: 99%